FINASTERIDE IN MODERN MEDICINE: THERAPEUTIC APPLICATIONS AND SYSTEMIC HEALTH IMPLICATIONS - Aleksandra Kutaj; Wiktor Łapa; Tatyana Savitskaya; Maria Sobolewska; Olga Magdalena Tuleja; Dawid Wiczkowski (International Journal of Innovative Technologies in Social Science, 2026)
Finasteride, a 5α-reductase inhibitor, is widely used for the treatment of androgenetic alopecia and benign prostatic hyperplasia. Its ability to reduce dihydrotestosterone (DHT) levels and promote hair growth has been well documented, making it a common therapeutic option among men. However, growing attention has been given to reports of persistent adverse effects affecting sexual, psychological, and metabolic health, which require further investigation. This review summarizes current findings on the dermatological and systemic effects of finasteride, emphasizing the need for comprehensive risk assessment and continued research. The literature review was conducted using the PubMed database, analyzing English-language studies published mainly between 2023 and 2025, identified with the keywords „finasteride”, „androgenetic alopecia”, „post-finasteride syndrome” and „adverse effects”. Despite these concerns, finasteride remains a clinically valuable and frequently prescribed medication for both androgenetic alopecia and benign prostatic hyperplasia. Reported persistent symptoms highlight the importance of proper patient education, informed consent, and individualized therapy. Further studies are required to clarify the mechanisms, prevalence, and management of these effects, ensuring safer and more informed clinical use of finasteride in both therapeutic and aesthetic contexts.